2005
DOI: 10.1063/1.1935432
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative evolution of a Na–Cl–NO[sub 3]–K–Ca–SO[sub 4]–Mg–Si brine at 95 °C: Experiments and modeling relevant to Yucca Mountain, Nevada

Abstract: A synthetic Topopah Spring Tuff water representative of one type of pore water at Yucca Mountain, NV was evaporated at 95°C in a series of experiments to determine the geochemical controls for brines that may form on, and possibly impact upon the long-term integrity of waste containers and drip shields at the designated high-level, nuclear-waste repository. Solution chemistry, condensed vapor chemistry, and precipitate mineralogy were used to identify important chemical divides and to validate geochemical calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Concentrated solutions are produced by many natural and artificial processes. Examples include water evaporation/boiling issues with nuclear waste disposal (Alai et al, 2005), seawater intrusion (Harvie and Weare, 1980;Harvie et al, 1984;Krumgalz, 2001), leakage of toxic solutions and electrolytic fluids from storage tanks (Lichtner et al, 2001 andSteefel et al, 2003;Zhang et al, 2005), and acid mine drainage (Blowes et al, 1991). The mathematical and numerical description of the nonidealities of concentrated aqueous solutions involves many nonlinear ioninteraction terms and various interaction parameter sets (e.g., Pitzer and Mayorga, 1973;Pitzer, 1991;Harvie et al, 1984;Wolery et al, 2004).…”
Section: Concentrated Aqueous Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrated solutions are produced by many natural and artificial processes. Examples include water evaporation/boiling issues with nuclear waste disposal (Alai et al, 2005), seawater intrusion (Harvie and Weare, 1980;Harvie et al, 1984;Krumgalz, 2001), leakage of toxic solutions and electrolytic fluids from storage tanks (Lichtner et al, 2001 andSteefel et al, 2003;Zhang et al, 2005), and acid mine drainage (Blowes et al, 1991). The mathematical and numerical description of the nonidealities of concentrated aqueous solutions involves many nonlinear ioninteraction terms and various interaction parameter sets (e.g., Pitzer and Mayorga, 1973;Pitzer, 1991;Harvie et al, 1984;Wolery et al, 2004).…”
Section: Concentrated Aqueous Solutionsmentioning
confidence: 99%
“…The implementation of the Pitzer model allows TOUGHREACT to deal with concentrated solutions, with limits on ionic strength, temperature, and pressure depending on the types and validity range of ion-interaction parameters in the thermodynamic database. The current thermodynamic database (after Wolery et al, 2004; see also Alai et al, 2005) is suitable for ionic strengths up to ~40 molal for some systems below 150°C at solution vapor saturation pressures, and is primarily intended for applications involving evaporative concentration at or below ~100°C. The Pitzer model in TOUGHREACT accounts for interaction terms of cation-anion, cation-neutral, anionneutral, cation-cation, anion-anion, cation-anion-anion, cation-cation-anion, neutral-cation-anion, neutral-cation-cation and neutral-anion-anion combinations (Appendix A).…”
Section: Toughreact Pitzer Ion-interaction Versions and Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity coefficients for dissolved gases such as CO 2 (aq) are computed from equations developed by Drummond (1981). Recently, a full Pitzer ion-interaction model was implemented as an option, using the formulation of Harvie et al (1984) (Zhang et al, 2006a,b; see also Zhang et al, 2004) and ion-interaction parameters re-evaluated and fitted as a function of temperature by Wolery et al (2004) (as published by Alai et al, 2005). Note that the latter data were modified to incorporate more suitable high-temperature data for CO 2(aq) from Rumpf et al (1994) and Rumpf and Maurer (1993), as discussed later.…”
Section: Toughreactmentioning
confidence: 99%
“…As previously, the computation was carried out using the database ThemXu4.dat for equilibrium constants of minerals and secondary species. The EQ3/6 data0.ypf database (Wolery et al, 2004, as published by Alai et al, 2005) is used for all Pitzer ion-interaction parameters, except for the CO 2(aq) parameters, which had to be revised for this study. Earlier simulations using the original data0.ypf database (André et al, 2006) showed that this database could not reasonably reproduce the solubility of calcite at temperatures above about 100°C.…”
Section: Toughreact With Pitzer Model (Tr-pitzer)mentioning
confidence: 99%